1999
DOI: 10.1021/om990567s
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Solid-State Properties of Self-Assembled Dinuclear Platinum(II) and Palladium(II) Rhomboids from Carbon and Silicon Tectons

Abstract: Self-assembly reactions of hitherto unknown bis(4-pyridyl)silanes 2a,b with bis(triethylphosphine)platinum and bis(triethylphosphine)palladium bistriflates 5a,b lead to the formation of new silicon-containing rhomboids 6a−d. In addition, a similar carbon analogue 7 was prepared by reaction of bispyridyl acetal 4 and bis(triethylphosphine)platinum bistriflate (5a). Surprisingly, reaction of the bis(4-pyridyl)ketone (3) and the platinum complex 5a gave a similar rhomboid, 10, due to unexpected hydration of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 32 publications
4
59
0
5
Order By: Relevance
“…[11][12][13][14][15] The silicon-containing pyridyl spacer ligands have been found to be useful for the synthesis of target skeletons since they are adjustable in bridging ability and length, possess flexible angles around silicon, and are conformationally nonrigid. [16][17][18][19][20] Certainly, some palladium(II) complexes have been known to be very good catalysts for various organic reactions. 21 Nonetheless, the catalytic reaction of well-defined metallamacrocycles remains an important issue with regard to the development of advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The silicon-containing pyridyl spacer ligands have been found to be useful for the synthesis of target skeletons since they are adjustable in bridging ability and length, possess flexible angles around silicon, and are conformationally nonrigid. [16][17][18][19][20] Certainly, some palladium(II) complexes have been known to be very good catalysts for various organic reactions. 21 Nonetheless, the catalytic reaction of well-defined metallamacrocycles remains an important issue with regard to the development of advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…Biological and synthetic porphyrins are of increased interest due to their use in the design and build-up of supramolecular structures, some of which have been applied successfully in various nanotechnological applications [12][13][14]. One particular interest is the use of porphyrins for spin-dependent electron transport through biomolecular devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that various silicon-containing pyridyl spacers are useful for the synthesis of task-specific skeletal structures, [20][21][22][23] since the ligands have been known to be adjustable in their potential bridging ability, flexible interligand angles at silicon, and conformers, in addition to the inductive and steric effects of the silicon atom. 24 In order to explore subtle difference between nickel(II) and copper(II) ions on molecular construction, we report the structures and related properties of the metal complexes prepared by the reaction of MX 2 (M = Ni(II), Cu(II)) with 1,2-bis(dimethyl-3-pyridylsilyl)ethane (L). L is a spacer ligand that possesses a flexible alkyl chain between two pyridine rings, a Present address: Department of Chemistry, Korea Air Force Academy, Chungbuk 363-840, Korea thereby imparting a conformational nonrigidity to the pyridyl groups.…”
Section: Introductionmentioning
confidence: 99%